An older, more quiescent universe from panchromatic SED fitting of the 3D-HST survey. Issue Volume 15:Issue S352(2019) (June 2019) - Leja, Joel; Johnson, Benjamin D.; Conroy, Charlie; van Dokkum, Pieter; Speagle, Joshua S.
Abstract: Galaxies are complicated physical systems which obey complex scaling relationships; as a result, properties measured from broadband photometry are often highly correlated, degenerate, or both. Therefore, the accuracy of basic properties like stellar masses and star formation rates (SFRs) depend on the accuracy of many second-order galaxy properties, including star formation histories (SFHs), stellar metallicities, dust properties, and many others. Here, we re-assess measurements of galaxy stellar masses and SFRs using a 14-parameter physical model built in the Prospector Bayesian inference framework. We find that galaxies are ∼0.2 dex more massive and have ∼0.2 dex lower star formation rates than classic measurements. These measurements lower the observed cosmic star formation rate density and increase the observed buildup of stellar mass, finally bringing these two metrics into agreement at the factor-of-two level at 0.5 < z < 2.5.